Reduction of bundle sheath size boosts cyclic electron flow in C4Setaria viridis acclimated to low light. (31st August 2022) - Bellasio, Chandra; Ermakova, Maria
SUMMARY: When C4 leaves are exposed to low light, the CO2 concentration in the bundle sheath (BS) cells decreases, causing an increase in photorespiration relative to assimilation, and a consequent reduction in biochemical efficiency. These effects can be mitigated by complex acclimation syndromes, which are of primary importance for crop productivity but are not well studied. We unveil an acclimation strategy involving the coordination of electron transport processes. First, we characterize the anatomy, gas exchange and electron transport of C4 Setaria viridis grown under low light. Through a purposely developed biochemical model, we resolve the photon fluxes and reaction rates to explain how the concerted acclimation strategies sustain photosynthetic efficiency. Our results show that a smaller BS in low‐light‐grown plants limited leakiness (the ratio of CO2 leak rate out of the BS over the rate of supply via C4 acid decarboxylation) but sacrificed light harvesting and ATP production. To counter ATP shortage and maintain high assimilation rates, plants facilitated light penetration through the mesophyll and upregulated cyclic electron flow in the BS. This shade tolerance mechanism, based on the optimization of light reactions, is possibly more efficient than the known mechanisms involving the rearrangement of carbon metabolism, and could potentially lead to innovative strategies for crop improvement. Significance Statement: We mechanistically link the optical cross section of leaf compartments with the rate of electron transport, the engagement of cyclic electron flow, the relative rate of ATP and NADPH generation and fluxes through the carbon metabolism. The striking capacity of Setaria viridis to counter the decrease in light absorption in the bundle sheath with an increase of cyclic electron flow presents perhaps the most efficient mechanism of shade acclimation.